Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5194/hess-18-1073-2014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of auto- and heterotrophic picoplankton and associated viruses in Lake Geneva

Abstract: Abstract. Microbial dynamics have rarely been investigated in Lake Geneva, known as the largest lake in western Europe. From a 5-month survey, we report dynamic patterns of free-living virus, bacteria and small phytoplankton abundances in response to a variety of environmental parameters. For the first time, we fractionated the primary production to separate the contribution of different size-related biological compartments and measured both bacterial and viral production in addition to experiments conducted t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 60 publications
(56 reference statements)
3
20
0
Order By: Relevance
“…Consequently, it has been posited that declines in VBR are due to viral loss, for example by non-specific adsorption to particles (Maranger & Bird, 1995) or degradation after adsorption to humic substances (Anesio et al, 2004). Inversely, high VBR values have been attributed to high viral production Kellogg, 2010;Yoshida-Takashima et al, 2012;Pinto, Larsen & Casper, 2013;Engelhardt et al, 2014;Parvathi et al, 2014) or low viral decay (Mei & Danovaro, 2004;Danovaro et al, 2005;Williamson et al, 2007;Winter, Kerros & Weinbauer, 2009;Maurice et al, 2010;De Corte et al, 2012), which in some cases (e.g. in soil and sediments) could be an artifact of extraction procedures (Middelboe, Glud & Finster, 2003;Williamson, Radosevich & Wommack, 2005;Kimura et al, 2008;Williamson, 2011).…”
Section: Introduction: the Virus-to-prokaryote Ratio -Definition Amentioning
confidence: 97%
“…Consequently, it has been posited that declines in VBR are due to viral loss, for example by non-specific adsorption to particles (Maranger & Bird, 1995) or degradation after adsorption to humic substances (Anesio et al, 2004). Inversely, high VBR values have been attributed to high viral production Kellogg, 2010;Yoshida-Takashima et al, 2012;Pinto, Larsen & Casper, 2013;Engelhardt et al, 2014;Parvathi et al, 2014) or low viral decay (Mei & Danovaro, 2004;Danovaro et al, 2005;Williamson et al, 2007;Winter, Kerros & Weinbauer, 2009;Maurice et al, 2010;De Corte et al, 2012), which in some cases (e.g. in soil and sediments) could be an artifact of extraction procedures (Middelboe, Glud & Finster, 2003;Williamson, Radosevich & Wommack, 2005;Kimura et al, 2008;Williamson, 2011).…”
Section: Introduction: the Virus-to-prokaryote Ratio -Definition Amentioning
confidence: 97%
“…During the last decade, previous studies have partially identified the diversity, dynamics, or role (as mortality agents of picocyanobacteria) of cyano(myo)phages in French perialpine lakes (12,17,23,42,43). This body of work has suggested that the cyano(myo)phage community is diverse, displays marked seasonal variations, and is concentrated mainly in surface waters down to 20 m deep.…”
mentioning
confidence: 99%
“…A positive association would be explained by a direct dependence of the phages by the density of its main host, as previously described in a large number of ecosystems (e.g., De Araújo & Godinho, 2009;Barros et al, 2010;Ram et al, 2011;Ben Rhomdame et al, 2014;Parvathi et al, 2014). However, this relationship could be partially darkened by the interaction of other biological components, such as mixotrophic and heterotrophic nanoflagellates, which have been detected as important agents of bacterioplankton mortality (Hakspiel-Segura, 2005).…”
Section: Discussionmentioning
confidence: 99%